2005
DOI: 10.1207/s15516709cog2901_3
|View full text |Cite
|
Sign up to set email alerts
|

The Large‐Scale Structure of Semantic Networks: Statistical Analyses and a Model of Semantic Growth

Abstract: We present statistical analyses of the large-scale structure of 3 types of semantic networks: word associations, WordNet, and Roget's Thesaurus. We show that they have a small-world structure, characterized by sparse connectivity, short average path lengths between words, and strong local clustering. In addition, the distributions of the number of connections follow power laws that indicate a scale-free pattern of connectivity, with most nodes having relatively few connections joined together through a small n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

78
1,183
7
23

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,045 publications
(1,291 citation statements)
references
References 65 publications
78
1,183
7
23
Order By: Relevance
“…One way to measure associative relations is via free association norms, where one word is provided (the cue) and participants are asked to produce the first word that comes to mind (the target). Several studies have now shown that the number of cue words that produce a given target word in free association norms is correlated with children's age of acquisition of that target word (Hills, Maouene, Maouene, Sheya & Smith, 2009 ;Hills et al, 2010 ;Steyvers & Tenenbaum, 2005). In other words, if, in response to a broad range of cues, the word ball was produced more often as a target than zebra, then ball will tend to have an earlier age of acquisition.…”
Section: University Of Warwickmentioning
confidence: 99%
See 2 more Smart Citations
“…One way to measure associative relations is via free association norms, where one word is provided (the cue) and participants are asked to produce the first word that comes to mind (the target). Several studies have now shown that the number of cue words that produce a given target word in free association norms is correlated with children's age of acquisition of that target word (Hills, Maouene, Maouene, Sheya & Smith, 2009 ;Hills et al, 2010 ;Steyvers & Tenenbaum, 2005). In other words, if, in response to a broad range of cues, the word ball was produced more often as a target than zebra, then ball will tend to have an earlier age of acquisition.…”
Section: University Of Warwickmentioning
confidence: 99%
“…Two adult-directed corpora were chosen to capture the diversity of adult-directed language. One was the Santa Barbara Corpus of Spoken American English (SBC), parts 1-4, which contained approximately 250,000 words, taken from sixty discourse recordings between adults, ranging from personal conversations to university lectures (Du Bois & Englebretson, 2000-2005. The SBC corpus is similar to the CHILDES corpus in that it represents largely conversational speech in American English.…”
Section: E T H O Dmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to achieve this is graph representation, with roots in semantic network theory (Collins and Loftus, 1975;Collins and Quillian, 1969;Steyvers and Tenenbaum, 2005). Graphs are mathematical objects consisting of sets of nodes and sets of edges connecting the nodes.…”
Section: Semantic Graphs and Complex Networkmentioning
confidence: 99%
“…These word association networks typically exhibit small-world structures, with short average distances between words, together with strong local clustering [24,11], a property shared with lexigraphical spaces obtained from word co-occurances [13].…”
mentioning
confidence: 99%